Small-sided games in amateur players: rule modification with mini-goals to induce lower external load responses - Pascual Bujalance-Moreno; Pedro Ángel Latorre-Román; Antonio Martínez-Amat; Felipe García-Pinillos (Termedia Publishing House, 2021)
The aim of this study was to compare the acute physiological (i.e., heart rate-related variables) and neuromuscular responses (i.e., sprint and jump) and time-motion characteristics (i.e., external load variables) when modifying the game design (possession play vs. mini-goals without a goalkeeper) during 4-a-side in amateur senior football players. Male senior football players (n = 16) performed two formats of small-sided games (SSGs) in two different testing sessions (4-a-side with possession play and mini-goals rule). Differences in time-motion characteristics and physiological parameters of players were measured with the Global Positioning System (GPS), and tested before and after (pre- and post-SSG) for neuromuscular assessment. A repeated measures analysis of variance (ANOVA), with Bonferroni post-hoc test, showed that both SSG formats induced changes in sprint performance (before-after comparison) (p ≤ 0.05). Moreover, the results showed that the variables muscle oxygen saturation, rate of perceived exertion, 85-89% heart rate peak, total distance, total distances at low speed, total distances at high speed, m/min, accelerations at low speed, accelerations of ≥ 2.5 m.s-2, maximal speed, and average speed were statistically significantly different among game conditions. The players' performances are affected by the inclusion of mini-goals during 4 vs. 4 SSGs. The results provide useful information for training and task design that replicate specific physical demands (i.e., accelerations of ≥ 2.5 m.s-2, total distances at high speed or total distances at low speed).